Perspectives in translating microfluidic devices from laboratory prototyping into scale-up production - Cong, Hengji; Zhang, Nan (Biomicrofluidics, 2022)
Transforming lab research into a sustainable business is becoming a trend in the microfluidic field. However, there are various challenges during the translation process due to the gaps between academia and industry, especially from laboratory prototyping to industrial scale-up production, which is critical for potential commercialization. In this Perspective, based on our experience in collaboration with stakeholders, e.g., biologists, microfluidic engineers, diagnostic specialists, and manufacturers, we aim to share our understanding of the manufacturing process chain of microfluidic cartridge from concept development and laboratory prototyping to scale-up production, where the scale-up production of commercial microfluidic cartridges is highlighted. Four suggestions from the aspect of cartridge design for manufacturing, professional involvement, material selection, and standardization are provided in order to help scientists from the laboratory to bring their innovations into pre-clinical, clinical, and mass production and improve the manufacturability of laboratory prototypes toward commercialization.